Υπολογιστική και πειραματική μελέτη της αποδόμησης πολλαπλών δειγμάτων ανθρώπινου αρθρικού χόνδρου - Γκούμα, Σαββίνη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Μηχανολογικών Κατασκευών και Αυτομάτου Ελέγχου.Εργαστήριο Εμβιομηχανικής και Συστημικής Βιολογίας (μη θεσμοθετημένο), 2017)
The articular cartilage is an avascular, elastic tissue that is located between the bones participating in joints. This unique tissue can distribute the load that is applied on the human body and facilitate the frictionless movement of the bones. Its repair is difficult, after degeneration has occurred, due to its avascular nature, making the reinstatement of its original mechanical properties almost impossible. The limited use of the joint, as well as the pain the patient experiences when the articular cartilage is damaged, makes the understanding of the degeneration mechanism of crucial importance. This thesis presents the effect of cytokines and drugs on the degeneration of the human articular cartilage, using computational and experimental methods. At first, the computational analysis, labels 78 stimuli as anabolic, catabolic or control, based on the published phosphoproteomic and cytokine release data. The aim of this analysis, is to suggest cytokines that potentially have a significant effect on the regeneration/ deterioration equilibrium during cartilage degeneration. The second part of this thesis examines the effect of the enzymic and catabolic cytokine treatment on the degradation of multiple cartilage samples and presents its experimental quantification. This experimental study exploits the High throughput Degradation Device (HDD), that was developed by I. Panagiotopoulos in the Bioengineering and Systems Biology Lab of the NTUA (Department of Mechanical Engineering), by conducting mechanical indentation tests on cartilage samples, treated with various stimuli, in order to quantify their degradation. The instrument’s precision, the biological error induced by the different mechanical properties of the tested samples and the device’s ability to quantify the effect of different collagenase concentrations is also examined. Finally, this thesis defines an experimental protocol, for studying the effect of the catabolic cytokines (IL1-a, IL1-b and TNF-a) on cartilage samples, harvested from human femoral heads. The described experimental methods can be used for studying the effects of cytokines and drugs on the degeneration and degradation of the articular cartilage.